STRATEGI PENINGKATAN DAYA SAING RUMAH POTONG AYAM PT XYZ - Arli Arli; Arief Daryanto; Dudi S. Hendrawan (School of Business, Bogor Agricultural University (SB-IPB), 2012)
ABSTRACTThe objectives of this study were (1) analyzing the role of parties in the value chain that affect PT XYZ competitiveness, (2) identifying the RPA PT XYZ stakeholders’ key players, (3) analyzing internal and external (IE) factors that affects the competitiveness of RPA PT XYZ , (4) formulating strategic long term objectives and goals to increase the competitiveness of RPA PT XYZ , (5) analyzing strategies’ priorities and alternatives to improve the competitiveness of RPA PT XYZ . The method used in this study was descriptive analysis. The analysis tools used in this study were global value chain, stakeholders’ analysis, internal factor evaluation, external factor evaluation, IE Matrix, SWOT, and quantitative strategic planning matrix. Based on the results of global value chain analysis, stakeholders analysis, internal and external analysis, and the company’s visions and missions, the long term objectives are (a) to provide value added for customers, (b) to maximize business operation’s profit, (c) to increase stakeholders’ welfare, (d) to operate a sustainable business operation. Results on the IE Matrix and the SWOT analysis, the strategies that can be used to achieve the strategic long term objectives and goals are (a) to increase the effectiveness and the efficiencies of the supply chain management; (b) to implement performance evaluation on employees and business partners; (c) to strengthen the company’s image as a high quality domestic chicken-based food producer in Indonesia; (d) to enhance researches and developments; (e) to build strategic alliances with external live chicken suppliers; (f) promote the importance of animal protein consumption to Indonesian society. Three priority strategies resulted from QSPM analysis are create enhancing the effectiveness and efficiency of the supply chain, implementing performance evaluation on employees and business partners, and strengthen the company’s image as a high quality domestic chicken-based food company in Indonesia.Keywords: competitiveness, global value chain, poultry slaughterhouse, PT XYZABSTRAKTujuan penelitian ini adalah (1) menganalisis peran aktor-aktor di dalam rantai nilai Rumah Potong Ayam (RPA) PT XYZ yang berpengaruh terhadap daya saingnya, (2) menganalisis para pemain kunci dalam stakeholders RPA PT XYZ , (3) menganalisis faktor-faktor internal dan eksternal (IE) yang berpengaruh terhadap daya saing RPA PT XYZ , (4) memformulasikan tujuan dan sasaran jangka panjang strategik untuk meningkatkan daya saing RPA PT XYZ , (5) menganalisis alternatif dan prioritas strategi untuk meningkatkan daya saing RPA PT XYZ . Metode yang digunakan adalah analisis deskriptif. Analisis yang digunakan adalah global value chain, analisis stakeholder, internal factor evaluation, external factor evaluation, matriks IE, SWOT, dan quantitative strategic planning matrix. Hasil dari analisis global value chain, analisis stakeholders, analisis internal dan eksternal, dan visi-misi perusahaan, tujuan jangka panjang adalah (a) menyediakan nilai tambah bagi pelanggan, (b) memaksimalkan laba dari hasil operasi bisnis, (c) meningkatkan kesejahteraan stakeholders, (d) melakukan kegiatan sustainable business. Hasil matriks IE dan analisis SWOT, strategi untuk mencapai sasaran dan tujuan jangka panjang strategik adalah (a) meningkatkan efektivitas dan efisiensi manajemen rantai pasok; (b) mengimplementasikan evaluasi kinerja untuk pegawai dan partner bisnis; (c) memperkuat citra sebagai perusahaan domestik penghasil makanan olahan berbasis daging ayam berkualitas tinggi di Indonesia; (d) meningkatkan kegiatan penelitian dan pengembangan; (e) membangun aliansi strategik dengan pemasok ayam hidup eksternal; (f) melakukan sosialisasi mengenai pentingnya konsumsi protein hewani kepada masyarakat Indonesia. Tiga strategi prioritas dari analisis QSPM adalah meningkatkan efektivitas dan efisiensi rantai pasok, mengimplementasikan evaluasi kinerja untuk pegawai dan partner bisnis, dan memperkuat citra perusahaan sebagai perusahaan domestik penghasil makanan olahan berbasis daging ayam berkualitas tinggi di Indonesia.Kata kunci: daya saing, rantai nilai global, rumah potong ayam, PT XYZ